Effect of inhaled sulphur dioxide and carbon particles on heart rate variability and markers of inflammation and coagulation in human subjects. Issue 2 (27th May 2005) - Routledge, H C; Manney, S; Harrison, R M; Ayres, J G; Townend, J N
Abstract : Objective: To measure the inflammatory and autonomic responses of healthy humans and patients with coronary artery disease to controlled concentrations of two specific components of vehicle derived air pollution, carbon particles and sulphur dioxide (SO2 ). Methods: Placebo controlled, double blind, random order human challenge study examining the effects of carbon particles (50 μg/m 3 ) and SO2 (200 parts per billion (ppb)) on heart rate variability (HRV) and circulating markers of inflammation and coagulation in healthy volunteers and patients with stable angina. Results: In healthy volunteers, markers of cardiac vagal control did not fall in response to particle exposure but, compared with the response to air, increased transiently immediately after exposure (root mean square of successive RR interval differences (RMSSD) 15 (5) ms with carbon particles and 4 (3) ms) with air, p < 0.05). SO2 exposure resulted in no immediate change but a significant reduction in HRV markers of cardiac vagal control at four hours (RMSSD −2 (3.6) ms with air, −7 (2.7) ms with SO2, p < 0.05). No such changes were seen in patients with stable angina. Neither pollutant caused any change in markers of inflammation or coagulation at zero, four, or 24 hours. Conclusion: In healthy volunteers, short term exposure to pure carbon particles does not cause adverse effects on HRV or a systemic inflammatory response. The adverse effects of vehicle derived particulates are likely to be caused by more reactive species found on the particle surface. SO2 exposure does, however, reduce cardiac vagal control, a response that would be expected to increase susceptibility to ventricular arrhythmia.